Effects of quebracho tannin extract (Schinopsis balansae Engl.) and activated charcoal on nitrogen balance, rumen microbial protein synthesis and faecal composition of growing Boer goats. Issue 4 (3rd July 2016) - Al-Kindi, Amal; Dickhoefer, Uta; Schlecht, Eva; Sundrum, Albert; Schiborra, Anne
ABSTRACT: Under irrigated arid conditions, organic fertiliser rich in slowly decomposable nitrogen (N) and carbon (C) is needed for soil fertility maintenance. Feeding ruminants with condensed tannins will lower ruminal protein degradation, reduce urinary N excretion and might increase the faecal fraction of slowly decomposable N. Supplementation with activated charcoal (AC) might enrich manure with slowly degrading C. Therefore, we investigated the effects of feeding quebracho tannin extract (QTE) and AC on the N balance of goats, the efficiency of microbial protein synthesis in the rumen (EMPS) and the composition of faeces. The feeding trial comprised three periods; in each period, 12 male Boer goats (28 ± 3.9 kg live weight) were assigned to six treatments: a Control diet (per kg diet 500 g grass hay and 500 g concentrate) and to further five treatments the Control diet was supplemented with QTE (20 g and 40 g/kg; diets QTE2 and QTE4, respectively), with AC (15 g and 30 g/kg, diets AC1.5 and AC3.0, respectively) and a mixture of QTE (20 g/kg) plus AC (15 g/kg) (diet QTEAC). In addition to the N balance, EMPS was calculated from daily excretions of purine derivatives, and the composition of faecal N was determined. There was no effect of QTE and AC supplementation on the intake of organic matter (OM), N and fibre, but apparent total tract digestibility of OM was reduced ( p  = 0.035). Feeding QTE induced a shift in N excretion from urine to faeces ( p  ≤ 0.001) without altering N retention. Total N excretion tended to decrease with QTE treatments ( p  = 0.053), but EMPS was not different between treatments. Faecal C excretion was higher in QTE and AC treatments ( p  = 0.001) compared with the Control, while the composition of faecal N differed only in concentration of undigested dietary N ( p  = 0.001). The results demonstrate that QTE can be included into diets of goats up to 40 g/kg, without affecting N utilisation, but simultaneously increasing the excretion of slowly decomposable N and C fractions. Feeding AC up to 30 g/kg of the diet increases slowly degradable faecal C concentration, without negative effects on N metabolism of goats.